A Pragmatic Analysis of Doctor Strange's Directive Utterances in Doctor Strange in the Multiverse of Madness Movie - Fitriana, Irta; Andani, Shifa Tri (Pioneer: Journal of Language and Literature, 2023)
This study aims to identify the directive speech act used by Doctor Strange as a main character based on the theory proposed by Yule and to explain how the directives in the movie Doctor Strange in the Multiverse of Madness are applied. This research applied descriptive qualitative study and used the movie as the object. The study used the protagonists directive utterances as data. The results showed four types of directive speech acts: commanding, ordering, requesting, and suggesting. The study showed that 50 directive utterances consisted of 16 data of commanding, 17 data of ordering, 12 data of requesting, and 5 data of suggesting. After analyzing 50 data, it was found that ordering was the most dominant type of Doctor Strange's directive utterances in the movie Doctor Strange in the Multiverse of Madness. It indicated that Doctor Strange had all the power to fight against the enemy and was stronger than others.